Internalization of ESQ Values in Building Entrepreneurial Character and Work Ethic: A Study on Sasirangan MSME Entrepreneurs in South Kalimantan - Rusdiana Rusdiana; Fahmi Hamdi; Salamah Salamah (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze the internalization of Emotional Spiritual Quotient (ESQ) values in building entrepreneurial character and work ethic among Sasirangan MSME entrepreneurs in South Kalimantan. The study is based on the assumption that entrepreneurial success is not only determined by technical and managerial competencies, but also by emotional intelligence, spiritual awareness, and cultural values that shape business behavior. The internalization of ESQ values is considered essential in strengthening entrepreneurial resilience, integrity, discipline, creativity, and ethical work orientation among local entrepreneurs engaged in the Sasirangan industry as a cultural-based creative economy sector. This research employs a qualitative approach using the Library Research method. Data were collected from scientific journals, books, theses, dissertations, and academic documents related to ESQ, Islamic entrepreneurship, work ethic, Banjar culture, and the development of Sasirangan MSMEs. The collected data were analyzed through content analysis to identify conceptual patterns and relationships between emotional intelligence, spiritual intelligence, entrepreneurial character, and work ethic. The findings reveal that the internalization of ESQ values significantly contributes to the formation of entrepreneurial character through honesty, responsibility, discipline, emotional control, creativity, and social awareness. Furthermore, spiritual intelligence strengthens the Islamic work ethic by encouraging entrepreneurs to perceive work as a form of worship, thereby increasing motivation, perseverance, and professional integrity. Banjar cultural values such as kayuh baimbai also reinforce cooperation, solidarity, and collective responsibility among Sasirangan entrepreneurs. The novelty of this study lies in its integrative analysis of ESQ values, Islamic spirituality, and Banjar local culture in shaping entrepreneurial character and work ethic within the context of Sasirangan MSMEs. This research also offers a conceptual contribution to Islamic entrepreneurship studies by emphasizing the importance of emotional-spiritual intelligence and local wisdom as socio-cultural capital for sustainable creative economic development.